Loss of CAMK2G affects intrinsic and motor behavior but has minimal impact on cognitive behavior - Rigter, Pomme M. F.; de Konink, Charlotte; van Woerden, Geeske M. (Frontiers in Neuroscience, 2023)
The gamma subunit of calcium/calmodulin-dependent protein kinase 2 (CAMK2G) is expressed throughout the brain and is associated with neurodevelopmental disorders. Research on the role of CAMK2G is limited and attributes different functions to specific cell types. To further expand on the role of CAMK2G in brain functioning, we performed extensive phenotypic characterization of a Camk2g knockout mouse. We found that the different CAMK2G isoforms show a distinct spatial expression pattern in the brain. Additionally, based on our behavioral characterization, we conclude that CAMK2G plays a minor role in hippocampus-dependent learning and synaptic plasticity. Rather, we show that CAMK2G is required for motor function, and that loss of CAMK2G results in impaired nest building and marble burying behavior, which are innate behaviors that are associated with impaired neurodevelopment. Taken together, our results provide evidence for a unique function for this specific CAMK2 isozyme in the brain and further support a role for CAMK2G in neurodevelopment.